Developing Creative Business Brands for Entrepreneurial Students through Differentiation and Positioning Strategies - Hadiahti - Utami; Budi - Prasetya; Sri Marheni Salsiyah; Sri Eka Sadriatwati; Erika - Devie (Politeknik Negeri Semarang, 2019)
This study aims to identify product differentiation and positioning strategies to obtain competitive advantage and to find out product differentiation and positioning strategies in building brand excellence against competitors. The research sample is the Entrepreneurial Student Creative Business Unit in the city of Semarang. The number of respondents in this study was 30 respondents. Data collection techniques in this study used observation, semistructured interviews and documentation. While the data analysis used the Triangulation Method. In this study, data were examined by the GDP strategy of triangle (Positioning, Differentiation and Brand) from Hermawan Kartajaya, data of entrepreneurial creative business activities, and data obtained from semistructured interviews with informants of owners or managers of entrepreneurial student creative businesses. The results showed that differentiation strategies could be identified based on product differentiation, service differentiation, channel differentiation, people differentiation and image differentiation. While the product positioning strategy was identified based on customer, company, competitors and change. By implementing a differentiation strategy and product positioning that is in accordance with the business it manages, it is expected that the business will have the desired competitive advantage, so that it can become the provision and strength to win in competition. Building a brand / brand through the application of the triangle theory of GDP (Positioning, Differentiation and Brand), has been done without being realized by entrepreneurial students. It is evident that some brands / brands of entrepreneurial students who are respondents in this study have credibility and are positively perceived by consumers so that their business can last a long time, their brands/brands are known to customers, easy to remember, reflect quality, of whis customers we able to differentiate the products morever from other and make multiple purchases to become loyal. Brands / brands like this can be used as a provision and strength of competitiveness to win the competition, and become the foundation for the company's competitive advantage